Japan Decides 2021
XXVI, 400 p. 49 illus., 2 illus. in color.
Keywords: Recent elections in Japan have been dramatic, and the 2021 general election was no exception. Worldwide turmoil caused by the coronavirus (COVID-19) pandemic, as well as domestic uncertainty following the resignation of long-serving Liberal Democratic Party (LDP) Prime Minister Abe Shinzō, left many voters and political observers wondering whether his successors were up to the task of leading the country through the crisis. In the end, the LDP and coalition partner Kōmeitō eked out an electoral victory—but one that masks important changes in the party system and nuanced changes in voter behavior and preferences. This fourth volume in the Japan Decides series features a comprehensive collection of analyses from leading experts, covering the legacy of Abe’s tenure in office, the state of the LDP and other parties, the impact of COVID-19 and the postponed 2020 Tokyo Summer Olympics, and many other important topics in contemporary party politics and domestic and foreignpolicy. Robert J. Pekkanen is Professor in the Henry M. Jackson School of International Studies, Adjunct Professor of Political Science, and Adjunct Professor of Sociology at the University of Washington, USA. Steven R. Reed is Professor Emeritus, retired from Chuo University, Japan. Daniel M. Smith is the Gerald L. Curtis Visiting Associate Professor of Modern Japanese Politics and Foreign Policy in the Department of Political Science and School of International and Public Affairs at Columbia University, USA.